2005
DOI: 10.1111/j.1399-0012.2005.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of diabetes mellitus in patients with cystic fibrosis undergoing lung transplantation before and after lung transplantation*

Abstract: Cystic fibrosis (CF) related diabetes mellitus (DM) occurs in 15% of adult pancreatic insufficient CF patients. Lung transplantation is a treatment option for end-stage CF. We hypothesized that the prevalence of DM increases after lung transplantation. The study population included adult patients undergoing lung transplantation from March 1988 to March 2002 for end-stage CF at the University of Toronto. Demographic data, exocrine pancreatic function, presence of DM before and after transplant, as well as timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 14 publications
2
58
1
1
Order By: Relevance
“…Moreover, a K ATP channel mutation is responsible for persistent hyperinsulinemia-hypoglycemia in infancy in humans (41). Similarly, patients with cystic fibrosis often develop diabetes (42,43). This further supports a role for glucose-excited and glucose-inhibited neurons (and the K ATP and CFTR channels) in the regulation of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, a K ATP channel mutation is responsible for persistent hyperinsulinemia-hypoglycemia in infancy in humans (41). Similarly, patients with cystic fibrosis often develop diabetes (42,43). This further supports a role for glucose-excited and glucose-inhibited neurons (and the K ATP and CFTR channels) in the regulation of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 76%
“…To the best of our knowledge, however, this study is the first to observe the evolution of metabolic control in pre-existing CFRD following LT. A few studies have focused on the development of CFRD at this stage. In a retrospective study of 77 CF patients with pancreatic insufficiency undergoing LT, Hadjiliadis et al [14 ]confirmed a significant increase in the prevalence of CFRD from 28.6% before transplantation to 49.4% after transplantation (p = 0.008). Similarly, Navas de Solis et al [17 ]compared 20 diabetic CF patients undergoing LT to another 34 diabetic CF patients and found a significantly higher rate of glucose intolerance or CFRD in the transplant patients (89 vs. 53% in the other patients), along with higher insulin requirements among the transplant patients (78.6 vs. 36.3%).…”
Section: Discussionmentioning
confidence: 90%
“…Among patients whose endogenous insulin secretion has been greatly affected, LT may cause a significant imbalance of diabetes, which exacerbates morbidity and mortality after transplantation by increasing the risk of infection and rejection [6,14,15]. Indeed, CF patients who undergo LT risk developing impaired glucose tolerance and CFRD as a result of immunosuppressive drugs and the stress induced by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have stressed the importance of the perioperative period in the renal evolution of lungtransplant patients, identifying prolonged mechanical ventilation and the utilization of amphotericin B as predictive factors for acute renal failure in the perioperative period (15). (16). Also poorly understood is the role of the antibiotics used in these patients.…”
Section: Most Authors Have Attributed the Development Of Chronic Kidnmentioning
confidence: 99%